Adolescent family perceptions in the At‐Risk Mental State for psychosis. Issue 4 (29th November 2013) - Welsh, Patrick; Tiffin, Paul A.
Abstract: Aim: There is a long‐standing interest in the relationship between patients affected by psychosis and their families. Previous research also suggests that perceived family dysfunction is a factor commonly associated with psychological problems in adolescence. The current study examined the role of self‐reported family perceptions in the context of adolescents with an At‐Risk Mental State (ARMS) for psychosis. Methods: Family perceptions were obtained using the Family Perceptions Scale (FPS) and compared across three groups; an ARMS for psychosis group ( n  = 44), a first‐episode affective/non‐affective psychosis group ( n  = 26) and a control group ( n  = 140) drawn from a community population. Results: Scores on the FPS  Expressed Emotion subscale were significantly higher in the psychosis and ARMS groups, compared to controls ( P  = 0.039 and P  = 0.041, respectively). In contrast, participants in the ARMS group reported poorer perceived problem solving and lower levels of nurturing behaviour in their families compared to controls ( P  = 0.032 and P  = 0.027). Overall, family perceptions were not related to symptom severity in both the ARMS and psychosis groups (except for manic symptomatology and Expressed Emotion ). Conclusions: These findings highlight that ARMS patients are likely to report higher levels of perceived family dysfunction compared to a community sample of young people. However, the mechanisms by which family perceptions may contribute to the development of distressing psychotic symptoms remain unclear and require further study. Family work, with a focus upon improving perceived expressed emotion, nurturing behaviours and hostility may at this stage represent a feasible adjunct therapy for those with ARMS.